Individual-based modeling of soil organic matter in NetLogo: Transparent, user-friendly, and open. (September 2015) - Banitz, Thomas; Gras, Anna; Ginovart, Marta
Abstract: Soil organic matter dynamics are essential for terrestrial ecosystem functions as they affect biogeochemical cycles and, thus, the provision of plant nutrients or the release of greenhouse gases to the atmosphere. Most of the involved processes are driven by microorganisms. To investigate and understand these processes, individual-based models allow analyzing complex microbial systems' behavior based on rules and conditions for individual entities within these systems, taking into account local interactions and individual variations. Here, we present a streamlined, user-friendly and open version of the individual-based model INDISIM-SOM, which describes the mineralization of soil carbon and nitrogen. It was implemented in NetLogo, a widely used and easily accessible software platform especially designed for individual-based simulation models. Including powerful means to observe the model behavior and a standardized documentation, this increases INDISIM-SOM's range of potential uses and users, and facilitates the exchange among soil scientists as well as between different modeling approaches. Highlights: We present a NetLogo version of an established IBM of SOM dynamics driven by microbes. The model was made simpler and less specific to increase its application potential. Users may easily access, explore and also modify the computational model. We provide the first complete standardized model description of INDISIM-SOM. The overall aim is an improved understanding of carbon and nitrogen dynamics in soils.